Smart Lighting and Energy Management System using Visitor Counter Based on IoT - Ishak, Muhammad Shazminshah; Ramli, Khairun Nidzam (Evolution in Electrical and Electronic Engineering, 2024)
This project explores the development of a Smart Light Energy Management system utilizing a visitor counter based on IoT technology. The increasing demand for energy-efficient solutions in modern buildings underlines the need for intelligent systems capable of optimizing energy consumption. Traditional lighting systems often lead to unnecessary energy usage due to manual operation and lack of integration with occupancy detection. The primary objective of this project is to design and implement an automated lighting control system that turns lights on or off based on real-time visitor counts. The methodology involves using a Durian Uno V3 microcontroller, IR infrared sensors for detecting visitor entry and exit, a relay module for light control, and an LCD I2C display for real-time status updates. The system also integrates with the Blynk app for remote monitoring and control. The novelty of this project lies in its simple yet effective approach to energy management, combining affordable components with IoT capabilities to create a responsive and user-friendly solution. The benefits to society include reduced energy wastage, lower electricity costs, and a step towards more sustainable building management practices.